Y-maze avoidance: An automated and rapid associative learning paradigm in zebrafish. (February 2015) - Aoki, Ryo; Tsuboi, Takashi; Okamoto, Hitoshi
Highlights: We developed a fully-automated learning paradigm for adult zebrafish. Learning is accomplished quickly (less than 2 h). Performance is very accurate in learner fish (correct at the rate of 89.0%). Our system is easily replicated and modified. Abstract: Adult zebrafish are gaining attention in behavioral neuroscience. By combining video tracking and computer-controlled visual cue presentations on a liquid crystal display screen under the tank, we have developed a new method by which zebrafish can be trained to avoid one arm of a Y-shaped tank by presenting a specific color on the floor paired with an electric shock. Within two hours, zebrafish learn to choose the correct arm at an efficiency of 89.0%. In addition, we also developed a graphical user interface to modify the paradigm assessment parameters such as shape of the tank and time schedules.